6(ax+ by)= 3a+2b, 6(bx-ay)=3b-2a

Asked by samridhi arora | 4th Jul, 2013, 03:26: PM

Expert Answer:

6(ax+by) = 3a + 2b   ____________________(1)

6(bx-ay) = 3b-2a  ______________________(2)

Add 1 and 2

a(6x-6y) + b(6x+6y) = a + 5b

Comparing both sides,

6x-6y = 1   _____________(3)

6x+6y = 5 ______________(4)

Adding 3 and 4

12x = 6

x = 1/2

y = 1/3

Answered by  | 4th Jul, 2013, 04:04: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.